FISHERY OF THE SWIMMING CFRAB PORTUNUS PELAGICUS LINNAEUS FROM PALK BAY AND GULF OF MANNAR - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
Fishery of Portunus pelagicus Linnaeus along the Palk Bay and Gulf Mannar is by a type of gill net locally known as nandu valai. They are also caught an large numbers in trawls operated by mechanised boats. The monthly catch pÂ«r unit effort at the three major crab fishing centres Devipattiaraam, Vedalai and Mandapam is estimated for three years and Vedialal* is- found to be the most productive centre for crabs. Some information regarding the marketing, disposal, longevity of life outside seai water aid sound production are also given